2000
DOI: 10.1093/jn/130.11.2780
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms of the Large Neutral Amino Acid L-Phenylalanine in the Human Intestinal Epithelial Caco-2 Cell Line

Abstract: The transepithelial transport and the intracellular accumulation of the large neutral amino acid L-phenylalanine (L-Phe) were studied in monolayers of Caco-2 cells, cultivated in a bicameral insert system, to characterize the mechanisms involved in the absorption of this essential amino acid by the human intestinal mucosa. In our model, L-Phe was transported selectively in the apical (AP)-to-basolateral (BL) direction. AP-to-BL transport of L-Phe was temperature dependent and Na(+) independent, increased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Once again, the results confirmed the interest in LNAA supplementation in the regulation of plasma Phe levels, most probably because of the competitive absorption of LNAA at the intestinal mucosa (Broer 2008). The competitive intestinal absorption of LNAA was verified using both rabbit and mouse intestinal tissue (Karasov et al 1986;Munck and Munck 1994;Stevens et al 1982) and human intestinal epithelial Caco-2 cells, where Phe and other LNAA were shown to compete for transport from the apical to the basolateral membrane (Berger et al 2000).…”
Section: Lnaa Supplementation In the Treatment Of Pku Patientssupporting
confidence: 70%
“…Once again, the results confirmed the interest in LNAA supplementation in the regulation of plasma Phe levels, most probably because of the competitive absorption of LNAA at the intestinal mucosa (Broer 2008). The competitive intestinal absorption of LNAA was verified using both rabbit and mouse intestinal tissue (Karasov et al 1986;Munck and Munck 1994;Stevens et al 1982) and human intestinal epithelial Caco-2 cells, where Phe and other LNAA were shown to compete for transport from the apical to the basolateral membrane (Berger et al 2000).…”
Section: Lnaa Supplementation In the Treatment Of Pku Patientssupporting
confidence: 70%
“…Nevertheless, a Na ϩ -independent transport component for neutral amino acids sensitive to BCH has been detected in the apical membrane of chicken, pig, and rabbit intestine (22,40,42). Moreover, Berger et al (1) reported that apical Na ϩ -independent L-phenylalanine uptake was mediated by systems b 0,ϩ and L in Caco-2 cells. Therefore, the results showing the inhibition of L-Met uptake by BCH in the absence of Na ϩ may confirm L activity across the apical membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid transport has also been studied in monolayers of Caco-2 cells. The results indicate that carrier-mediated transport of amino acids is significantly faster than their paracellular transport (141,148) or the transport of D-mannitol, which occurs entirely by the paracellular route (25,26). These studies used low concentrations of radiolabeled amino acids and therefore may underestimate paracellular transport at higher concentrations.…”
Section: Significance Of Paracellular Transportmentioning
confidence: 93%